Single anterior cervical discectomy and fusion (ACDF) using self- locking stand-alone polyetheretherketone (PEEK) cage: evaluation of pain and health-related quality of life - Kapetanakis, Stylianos; Thomaidis, Tryfon; Charitoudis, George; Pavlidis, Pavlos; Theodosiadis, Panagiotis; Gkasdaris, Grigorios (Journal of Spine Surgery; Vol 3, No 3 (September 29, 2017): Journal of Spine Surgery, 2017)
Background: Anterior cervical discectomy and fusion (ACDF) constitutes the conventional treatment of cervical disc herniation due to degenerative disc disease (DDD). ACDF with plating presents a variety of complications postoperatively and stand-alone cages are thought to be a promising alternative. The aim of this study was firstly, to analyze prospectively collected data from a sample of patients treated with single ACDF using C-Plus self-locking stand-alone PEEK cage system, without the use of plates or screws, in order to evaluate pain levels of patients, utilizing Neck and Arm Pain scale as an expression of visual analogue scale (VAS). Secondly, we aimed to evaluate health-related quality of life, via the short-form 36 (SF-36) and Neck Disability Index (NDI). Methods: Thirty-six patients (19 male and 17 female) with mean age 49.6±7 years old who underwent successful single ACDF using self-locking stand-alone PEEK cage for symptomatic cervical DDD were selected for the study. Neck and Arm pain, as well as SF-36 and NDI were estimated preoperatively and 1, 3, 6, and 12 months postoperatively. Patients underwent preoperative and postoperative clinical, neurological and radiological evaluation. Results: The clinical and radiological outcomes were satisfactory after a minimum 1-year follow-up. All results were statistically important (P